Four Pilars of Nationality Strengthen the Unitary Republic of Indonesia - Arifin, Mahar; Sinaga, Obsatar (International Journal of Psychosocial Rehabilitation, 2020)
The four pillars of nationality are the four pillars of support in a country, whereas the pillars are connected to one another. The strength of the Republic of Indonesia finally passed away on whether we still use the four pillars of nationalism. The four pillars of the Republic of Indonesia, namely Pancasila as the basis and ideology of the state, the 1945 Constitution of the Republic of Indonesia as a state constitution and the decree of the republic of Indonesia, the Republic of Indonesia, the republic of Indonesia as a form of state, and Unity in Diversity as the motto of the country. The paradigm of a society that is so active, dynamic, and national today is access to social changes that occur in the community, both as a consequence of the demands of the times and the development of an increasingly open, critical, and universal mindset of society. Changes in the dynamics require the MPR RI to make adjustments, mainly related to the position of the institutional task and authority.